Variability in parasites’ community structure and composition in cat fish with respect to level of pollution in Mwanza Gulf, Lake Victoria, Tanzania - Mwita, C. J. (Tanzania Journal of Science, 2021)
This study investigated the composition and structure of the parasite communities in Cat fish with respect to levels of water pollution in Lake Victoria. A total of 1071 Clarias gariepinus with mean TL range of 19 to 27 cm were analyzed from three localities in Mwanza Gulf (Kirumba, 298 fish infected with 15 parasite species), Nyegezi (376 fish, with 15 parasites species) and Malimbe (397 fish, with 16 parasites species). Trematodes and nematodes dominated the population with six (35.3%) and five (29.4%) species, respectively. Mean species richness and heteroxenous/monoxenous ratio showed significant changes (Fr = 8.000; p = 0.0046), being high at Malimbe and declining towards Kirumba Bay. Contracaecum species dominated the gut parasites with higher load per infected fish at Kirumba Bay than the other two sites. The observed composition and structural changes among the sites studied are linked to an increase in untreated waste water discharge as a result of higher population density in the Kirumba Bay watershed as opposed to the other localities.